2015
DOI: 10.1002/jcb.25215
|View full text |Cite
|
Sign up to set email alerts
|

In situ Analysis of Smoothelin‐like 1 and Calmodulin Interactions in Smooth Muscle Cells by Proximity Ligation

Abstract: The smoothelin-like 1 (SMTNL1) protein is the newest member of the smoothelin family of muscle proteins. Two calmodulin (CaM)-binding domains (CBD1 for Ca-CaM; CBD2 for apo-CaM) have been described for the SMTNL1 protein using in vitro assays. We now demonstrate in situ associations of SMTNL1 and CaM in A7r5 smooth muscle cells using the proximity ligation assay (PLA). We quantified CaM-SMTNL1 proximity events accurately after taking into account variations in protein expression levels. The refined method allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…Conversely, SMTNL1 phosphorylation during calcium desensitization of smooth muscle could provide enhanced binding to Tpm and restrict binding of CaM in the apo-state, securing phosphorylated SMTNL1 with Tpm on the thin filament. The weak binding modes of SMTNL1 with apo-CaM might not possess enough stability to occur in vivo [12]. While the physiological significance of SMTNL1 association with the contractile filament in situ has not been investigated, we speculate that the protein may act in analogous manners to caldesmon or calponin on actin-myosin cross bridge cycling.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Conversely, SMTNL1 phosphorylation during calcium desensitization of smooth muscle could provide enhanced binding to Tpm and restrict binding of CaM in the apo-state, securing phosphorylated SMTNL1 with Tpm on the thin filament. The weak binding modes of SMTNL1 with apo-CaM might not possess enough stability to occur in vivo [12]. While the physiological significance of SMTNL1 association with the contractile filament in situ has not been investigated, we speculate that the protein may act in analogous manners to caldesmon or calponin on actin-myosin cross bridge cycling.…”
Section: Discussionmentioning
confidence: 95%
“…This agrees with our observation that the rate of PKA-dependent phosphorylation at Ser301 was not influenced when apo- or Ca-CaM was included in the kinase assay (unpublished results). We have previously demonstrated that intramolecular interactions between the C -terminal IQ motif (localization of the apo-CaM binding site, CBD2) and the intrinsically disordered region (localization of the phosphorylation site) influence apo-CaM binding [11, 12]. Furthermore, a portion of the N -terminal intrinsically disordered region forms intramolecular contacts with the globular C -terminal calponin homology (CH) domain [18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations